Reform of the Conflict-of-Interest Regulations for Judges in Judicial Mafia Practices to Guarantee the Independence of the Judicial Power - Widodo; Suparno (Journal of Legal and Cultural Analytics, 2026)
This study aims to analyze the provisions on judicial conflicts of interest in Indonesian positive law and formulate a reconstruction of these provisions as an effort to strengthen the independence of the judiciary. The method used is normative juridical research with a statutory and conceptual approach, through a review of the 1945 Constitution of the Republic of Indonesia, Law Number 48 of 2009 concerning Judicial Power, and the Code of Ethics and Guidelines for Judicial Conduct. The results of the study indicate that although there are provisions regarding judicial independence and the prohibition of conflicts of interest, the existing norms are still general in nature, lack clear operational definitions, and are not supported by effective disclosure and recusal mechanisms. This condition opens up space for the practice of judicial mafia, which has an impact on declining public trust in the judiciary. Therefore, a reconstruction of the provisions on judicial conflicts of interest is needed through affirmation of norms, strengthening disclosure and resignation mechanisms, and integrating a more transparent and accountable oversight system. This research is expected to provide theoretical contributions to legal development and practical contributions to the reform of the judicial system in Indonesia.